Motivating children with specific learning difficulties a teacher's practical guide - Elbeheri, Gad; Reid, Gavin 1950-; Everatt, John (Routledge, 2018)
'Motivating Children with Specific Learning Difficulties' provides a comprehensive and definitive guide to what teachers need to know about motivation in pupils with specific learning difficulties, including dyslexia, dyspraxia and ADHD.